2015
DOI: 10.1007/s10006-015-0533-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the anti-inflammatory effect of dexamethasone and ketorolac in the extractions of third molars

Abstract: This double-blind, split-mouth, and randomized study was aimed to compare the efficacy of dexamethasone and ketorolac tromethamine, through the evaluation of pain, edema, and limitation of mouth opening. Thirty-four individuals aged 18-26 years, having bilateral mandibular third molars, in a similar position, were selected. Two different surgical procedures were performed on the same individual by the single surgeon. For an extraction, the individual received 1 capsule of 10 mg ketorolac tromethamine 1 h befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 37 publications
1
24
1
1
Order By: Relevance
“…Because of its analgesic and anti-inflammatory efficacy by inhibiting prostaglandin biosynthesis, ketorolac has been considered as an alternative to glucocorticoid in the postoperative period after oral surgery [ 9 20 21 ]. The anti-inflammatory efficacy of ketorolac, despite being inferior to its analgesic activity, was found to be approximately twice as great as that of indomethacin and 3 times as great as that of naproxen in terms of suppressing edema in an animal model [ 22 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its analgesic and anti-inflammatory efficacy by inhibiting prostaglandin biosynthesis, ketorolac has been considered as an alternative to glucocorticoid in the postoperative period after oral surgery [ 9 20 21 ]. The anti-inflammatory efficacy of ketorolac, despite being inferior to its analgesic activity, was found to be approximately twice as great as that of indomethacin and 3 times as great as that of naproxen in terms of suppressing edema in an animal model [ 22 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its great analgesic efficacy, ketorolac is commonly administered IV as a single dose or supplement to opioid analgesic to relieve acute postoperative pain. Both topical and oral administration of ketorolac have been reported an anti-inflammatory efficacy equivalent to that of dexamethasone by suppressing acute pain and swelling after cataract and dental procedures [ 8 9 ]. However, no single study has compared the anti-inflammatory efficacies of intravenous dexamethasone and ketorolac in terms of the prevention of POST after thyroidectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative pain is one the greatest concerns among patients and surgeons after third-molar extractions. Thus, postoperative pain evaluation is a study model extensively used to create drug clinical protocols that minimize the pain symptoms after dental surgeries (Mojsa et al, 2017;Barden, Edwards, McQuay, & Andrew Moore, 2004;Brignardello-Petersen, 2017) Corticosteroids are the most widely used drugs for preemptive analgesia in surgical practice, and several clinical trials have showed their effectiveness in reducing postoperative pain, edema, and trismus (Antunes, Avelar, Martins Neto, Frota, & Dias, 2011;Darawade, Kumar, Mehta, Sharma, & Reddy, 2014;Paiva-Oliveira et al, 2016;Simone, Jorge, Horliana, Canaval, & Tortamano, 2013). However, recent studies have shown that the combination of corticosteroids and NSAIDs may improve the postoperative symptoms after Development, v. 9, n. 9, e968997979, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.7979 third-molar surgeries, mainly the acute pain in the first hours (Bamgbose et al, 2005;Moore et al, 2005;Barbalho et al, 2017;Bauer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…4 The literature recommends 8mg dexamethasone, 1 hour before the surgical procedure. 10,11 These protocols are based on numerous clinical trials; however, there is insufficient scientific evidence to reach a consensus regarding the anti-inflammatory effectiveness of dexamethasone in mandibular third molar surgery, when using the same dose and route at different administration times. Considering the above, the aim of the present research was to compare the antiinflammatory effectiveness of dexamethasone as presurgical and post-surgical therapy in mandibular third molar surgery.…”
Section: Introductionmentioning
confidence: 99%